The relationship between early maladaptive schemas and burnout with the mediating role of psychological capital - Zahra Amini; Vahid Khoshravesh (Institute of Management fekrenoandish, 2020)
The aim of this study was to analyze the relationship between early maladaptive schemas and burnout with the mediating role of psychological capital. The research method was descriptive-correlational in nature and applied in terms of purpose. The statistical population of the study was primary school principals in Tehran engaged in service in the school year 1397-98. The sample size was determined 200 individuals and selected using a multi-stage cluster sampling method. For data collection, the Lutans (2007) Psychological Capital Questionnaire, Maslach & Jackson (1985) burnout questionnaires, and Young's early maladaptive schemas (2006) were used. Their validity was confirmed by experts and academics and their reliability was confirmed by Cronbach's alpha coefficient test. In order to analyze the data, the structural equation method was used using LISREL statistical software, eighth edition. The results showed an early maladaptive schema and its dimensions (cut and rejection, impaired self-control and function, impaired limitations, other orientation and excessive distraction and inhibition) have a negative relationship with psychological capital and its dimensions, and a positive and significant relationship with burnout. Psychological capital has a negative and significant relationship with burnout and finally, psychological capital has a mediating role in the relationship between initial maladaptive schemas and burnout.